1963
DOI: 10.1111/j.1365-2621.1963.tb01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins. IV. Anthocyanin Pigments of Cabernet Sauvignon Grapesa,b

Abstract: Six anthocyaninswere isolated from Cabernet Sauvignon grapes. Four major and one minor pigment were identified by paper chromatography, color reactions, and spectroscopy.The four major anthocyanins were identified as delphinidin-3-monoglucoside, petunidin-3-monoglucoside, malvidin-3monoglncoside, and malvidin-3-monoglueoside aeetylated with chlorogenic acid. Malvidin-3-monoglucoside was the most abundant pigment of the grapes. One of the minor pigments was identified as petnnidin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Cabernet Sauvignon grapes contain four major anthocyanins: delphinidin-3monoglucoside, petunidin-3-mono glucoside, malvidin-3-monoglucoside, and malvidin-3monoglucoside acetylated with chlorogenic acid. One of the major pigments is petunidin (Somaatmadja and Powers 1963). Anthocyanin pigments can easily be destroyed when fruits and vegetables are processed.…”
Section: Anthocyanins and Flavonoidsmentioning
confidence: 99%
“…Cabernet Sauvignon grapes contain four major anthocyanins: delphinidin-3monoglucoside, petunidin-3-mono glucoside, malvidin-3-monoglucoside, and malvidin-3monoglucoside acetylated with chlorogenic acid. One of the major pigments is petunidin (Somaatmadja and Powers 1963). Anthocyanin pigments can easily be destroyed when fruits and vegetables are processed.…”
Section: Anthocyanins and Flavonoidsmentioning
confidence: 99%
“…These substances and their derivatives have been shown by Powers et al to have measurable inhibitory activity against such organisms as Eberthella typhosa, Shigella dysenteriae, Salmonella enteriditis, and Staphylococcus aureus (Gardner, 1953;Masquelier, 1958;Somaatmadja and Powers, 1963).…”
Section: Tannins Pigments Polyphenolsmentioning
confidence: 99%
“…(1) and Somaatmad ja and Powers (20). Reuther (17) reported that diglucosides were characteristic of V. riparia and V. rupestris.…”
Section: Introductionmentioning
confidence: 99%